Evaluation of acute head injury by computed tomography scan in College of Medical Sciences-Teaching Hospital, Chitwan - Tayal, A; Chhetri, PK (Journal of College of Medical Sciences-Nepal, 2012)
This study was conducted to evaluate the computed tomography findings in patient with acute head injury and to emphasize the importance of computed tomography scan in head injury. One hundred consecutive patients presenting to the emergency department with head injury were evaluated by computed tomography scan of the head. Seventy five patients (75%) were male and twenty five (25%) were females. The age of the patients ranged from three to seventy years and the most affected age group was between thirty and forty (40%). The common causes of head injury were motor vehicle accident (70%), fall injury (25% ) and physical assault (5%). The most common computed tomographic findings were: cerebral contusions (52%), skull fractures (41%), intracerebral hematomas (24%), diffuse cerebral edema (23%), midline shift (18%), subdural hematomas (15%), subarachnoid hemorrhage (13%), diffuse axonal injury (8%), intraventricular hemorrhage (6%), extradural hemotomas (4%), pnemocephalus (2%) and normal scans were found in (5%). In conclusion, computed tomography is the mainstay in the imaging of head injury and helps in the patient management. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5971 JCMSN 2011; 7(1): 36-39